Corruption, provincial institutions and manufacturing firm productivity: New evidence from a transitional economy - Tuyen, Tran Quang; Huong, Vu Van; Tinh, Doan Thanh; Hiep, Tran Duc (Estudios de Economía, 2016)
Using data from nationwide surveys of provincial institutions and private manufacturing small medium enterprises, this study provided the first evidence of the impact of provincial institution quality and firms’ participation in and intensity of corrupt activities on firm productivity in Vietnam. We found that the bribe intensity instead of whether firms bribed state officials or not (measured by a dummy variable) has a negative effect on firm productivity when the endogeneity of corruption and unobservable characteristics are controlled for. This finding contrasts to a popular belief about a paradox for East Asian countries where corruption is positively associated with firm growth.